New records of Procellariiformes in the Fernando de Noronha archipelago: who is looking out for them? - Lucas Penna Soares Santos; Fábio Olmos; Taysa Alves Rocha; Maria Clara Gonçalves de Queiroz Brito; Gisiane Rodrigues Lima; Cecilia Licarião Barreto Luna; Rodrigo Augusto Torres; Ricardo Araujo; Patricia Pereira Serafini (Check List, 2024)
Little is known on seabirds of the order Procellariiformes which visit the Brazilian oceanic islands. Herein, we present new records of five birds found stranded in the Fernando de Noronha archipelago: Fregetta tropica melanoleuca Salvadori, 1908, Ardenna grisea (Gmelin, 1789), Puffinus lherminieri Lesson, 1839, and Hydrobates leucorhous (Vieillot, 1818). Citizen‑science platforms include only one documentation for each of these species, but there is potential for greater detection. Pelagic birds have rarely been reported in recent decades, and continued monitoring is needed for better understanding of their distribution patterns.